Robots Assist or Replace Teachers in the Classroom - Senad Orhani (Research Synergy Foundation, 2023)
As artificial intelligence and robotics technologies continue to grow exponentially, we will be able to do some amazing things with the help of robots in education. This article will describe the potential of robots in the education system. The use of robots in educating students can be crucial, but it remains uncertain whether they will entirely replace teachers. Therefore, this study aims to see if robots are assistants or replace teachers in the classroom. This study followed a systematic approach to the reviewed literature to compile relevant articles. Robots can be helpful teaching tools in the school, as evidenced by the results and pertinent literature, but it is unlikely that they will ever completely replace teachers. Robots, however, are a flexible solution for the educational system and are appropriate for some forms of assistance.